2011
DOI: 10.1007/s00436-011-2552-8
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, expression, and characterization of Schistosoma japonicum tegument protein phosphodiesterase-5

Abstract: The tegument proteins of schistosomes are regarded as potential vaccine candidates and drug targets to control schistosomiasis. Nucleotide pyrophosphatase/phosphodiesterase-5 (NPP-5), which belongs to a multigene family of nucleotide pyrophosphatase/phosphodiesterases (NPPs), is important in the hydrolysis of pyrophosphate or phosphodiester bonds in nucleotides and their derivatives. In the present study, SjNPP-5, identified as one of the tegument proteins of Schistosoma japonicum in our previous proteomic stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Human schistosomiasis is one of the most prevalent and serious parasitic diseases worldwide, with an estimated 200 million people currently diagnosed with the disease in tropical and subtropical regions (Wang et al 2009;Zhang et al 2012). Schistosomiasis is mainly caused by Schistosoma species japonicum, mansoni, and haematobium.…”
Section: Introductionmentioning
confidence: 99%
“…Human schistosomiasis is one of the most prevalent and serious parasitic diseases worldwide, with an estimated 200 million people currently diagnosed with the disease in tropical and subtropical regions (Wang et al 2009;Zhang et al 2012). Schistosomiasis is mainly caused by Schistosoma species japonicum, mansoni, and haematobium.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the T-cell immune response that was induced was counter-balanced by a strong regulatory response, characterized by TGF-β. Moreover, it has been demonstrated that immunization with NPP-5 from S. japonicum, resulted in a partial worm burden reduction following a subsequent challenge (Zhang et al, 2012a). Therefore it is possible that a properly folded protein would show a different result.…”
Section: Resultsmentioning
confidence: 99%
“…The vampire snail Colubraria reticulata secretes anticoagulants during feeding, and a protein similar to NPP5 is highly expressed in its salivary tissue [19]. In the parasitic flatworms Schistosoma mansoni and Schistosoma japonicum, which live in blood capillaries, an ortholog of NPP5 is also present, on the outer layer of the worm [20,21]. Interestingly, SmNPP5 can hydrolyze p-nitrophenyl-TMP [20,22] and was proposed to participate in catabolism of extracellular nucleotides [27].…”
Section: Substrate Bindingmentioning
confidence: 99%
“…In contrast, it was identified as an angiogenesisrelated gene in pediatric high-grade glioma [18]. Orthologs of this enzyme have been reported in the salivary tissue of the vampire snail which feeds on the blood of fish [19] and in parasitic flatworms that live in blood capillaries [20][21][22]. Metabolism of nucleotides in the circulation was proposed as a function for these homologs.…”
Section: Introductionmentioning
confidence: 99%